Tungsten target composite and method of making same
By ball milling and mixing spherical tungsten powder, titanium powder, sodium cellulose, polyvinyl alcohol with carbon nanotubes and flaky molybdenum disulfide, a tungsten target composite material with excellent conductivity and mechanical properties was prepared, which solved the shortcomings of pure tungsten material in conductivity and mechanical properties.
Patent Information
- Application Number
- CN202411990405.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-10-10
- Estimated Expiration
- 2044-12-31
AI Technical Summary
Pure tungsten materials cannot fully meet the requirements of specific application scenarios in terms of conductivity and mechanical properties.
A tungsten target composite material with excellent electrical conductivity and mechanical properties is formed by ball-milling spherical tungsten powder, spherical titanium powder, sodium carboxymethyl cellulose, and polyvinyl alcohol, adding a nitric acid solution of carbon nanotubes and aminosilane coupling agent, mixing them evenly, and combining them with flaky molybdenum disulfide powder. After ultrasonic treatment, degreasing and sintering, a tungsten target composite material with excellent electrical conductivity and mechanical properties is formed.
The electrical conductivity and mechanical properties of tungsten target composite materials are significantly improved, a three-dimensional conductive network is formed, the interface bonding strength is enhanced, the friction coefficient is reduced, the structure is optimized, and the material density and uniformity are improved.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of alloy materials, and in particular to a tungsten target composite material and a preparation method thereof. Background Art
[0002] As a metallic element with a high melting point and high density, tungsten has a wide range of applications in various fields. However, pure tungsten cannot fully meet the requirements of specific application scenarios in terms of certain properties, such as conductivity and mechanical properties.
[0003] Therefore, preparing tungsten composite materials by adding other elements or compounds to improve their performance has become a hot topic in current research. Summary of the Invention
[0004] The present invention provides a tungsten target composite material and a preparation method thereof. The tungsten target composite material has excellent electrical conductivity and mechanical properties and has broad application prospects.
[0005] The present invention solves its technical problems by adopting the following technical solutions:
[0006] A method for preparing a tungsten target composite material, characterized by comprising the following steps:
[0007] (1) Add spherical tungsten powder, spherical titanium powder, sodium carboxymethyl cellulose, and polyvinyl alcohol to water, and mix them evenly by ball milling to obtain a first mixed solution;
[0008] (2) adding carbon nanotubes and aminosilane coupling agent to the nitric acid solution and stirring evenly to obtain a second mixed solution;
[0009] (3) uniformly mixing the first mixed solution, flaky molybdenum disulfide powder, and the second mixed solution, ultrasonically treating, and drying to obtain a precursor;
[0010] (4) Degreasing and sintering the precursor to obtain a tungsten target composite material.
[0011] The present invention creatively mixes spherical tungsten powder, spherical titanium powder, sodium carboxymethyl cellulose and polyvinyl alcohol by ball milling, then mixes carbon nanotubes, aminosilane coupling agent and nitric acid solution, and then evenly mixes the first mixed solution, flaky molybdenum disulfide powder and the second mixed solution. Finally, after degreasing and sintering, a tungsten target composite material with excellent electrical conductivity and mechanical properties is obtained.
[0012] Among them, the present invention uses spherical tungsten powder as the main material, and the addition of spherical titanium powder can form a good interface bonding with carbon nanotubes and flaky molybdenum disulfide powder, improve the interface bonding strength of the composite material, and help form a three-dimensional conductive network. Carbon nanotubes, with their high conductivity and unique tubular structure, can form an efficient three-dimensional conductive channel, improve the transmission rate of electrons, and effectively improve the conductivity and mechanical properties. The addition of flaky molybdenum disulfide powder can lubricate the direct interface between spherical tungsten powder, spherical titanium powder and carbon nanotubes, reduce the friction coefficient between the materials, and optimize the wire network structure. The flaky molybdenum disulfide powder can form a layered structure in the composite material, which helps to disperse and absorb stress and improve the mechanical properties of the material. At the same time, the addition of spherical titanium powder and molybdenum disulfide powder can also increase the density and uniformity of the composite material, reduce pores and defects, and further reduce obstacles in the electron transmission process, and then under the synergistic effect of each component, effectively improve the conductivity and mechanical properties.
[0013] As a preferred embodiment of the present invention, the average particle size of the spherical tungsten powder is 100-200 nm.
[0014] As a preferred embodiment of the present invention, the average particle size of the spherical titanium powder is 80-150 nm.
[0015] As a preferred embodiment of the present invention, the mass ratio of the spherical tungsten powder, spherical titanium powder, sodium carboxymethyl cellulose, polyvinyl alcohol, and water is 1: (0.12-0.18): (0.02-0.06): (0.02-0.05): (4-10).
[0016] As a preferred embodiment of the present invention, the carbon nanotubes have a diameter of 15-30 nm and a length of 10-20 μm.
[0017] As a preferred embodiment of the present invention, the aminosilane coupling agent includes at least one of γ-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, and N-(2-aminoethyl)-3-aminopropyltriethoxysilane.
[0018] As a preferred embodiment of the present invention, the mass ratio of the carbon nanotubes, the aminosilane coupling agent, and the nitric acid solution is 1: (0.01-0.03): (4-10).
[0019] As a preferred embodiment of the present invention, the molar concentration of the nitric acid solution is 0.1~1 mol / L.
[0020] As a preferred embodiment of the present invention, the average particle size of the flaky molybdenum disulfide powder is 500 nm to 1000 nm.
[0021] As a preferred embodiment of the present invention, the mass ratio of the first mixed liquid, the flaky molybdenum disulfide powder, and the second mixed liquid is 1: (0.02-0.03): (0.2-0.3).
[0022] As a preferred embodiment of the present invention, the degreasing temperature is 540-580° C., and the degreasing time is 6-12 hours.
[0023] As a preferred embodiment of the present invention, the sintering temperature is 1180-1220° C., and the sintering time is 2-6 hours.
[0024] The present invention also provides a tungsten target composite material, which is prepared by the above-mentioned preparation method.
[0025] The beneficial effects of the present invention are as follows: the present invention mixes spherical tungsten powder, spherical titanium powder, sodium carboxymethyl cellulose and polyvinyl alcohol by ball milling, then mixes carbon nanotubes, aminosilane coupling agent and nitric acid solution, then uniformly mixes the first mixed solution, flaky molybdenum disulfide powder and the second mixed solution, and finally degreases and sinters to obtain a tungsten target composite material with excellent electrical conductivity and mechanical properties. DETAILED DESCRIPTION
[0026] To make the objectives, technical solutions, and advantages of the embodiments of the present invention more clear, the technical solutions in the embodiments of the present invention are clearly and completely described below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. All other embodiments obtained by ordinary technicians in this field based on the embodiments of the present invention without making any creative efforts shall fall within the scope of protection of the present invention.
[0027] In the present invention, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.
[0028] In the present invention, when referring to numerical ranges, unless otherwise specified, the numerical ranges are considered continuous and include the minimum and maximum values of the range, as well as every value between such minimum and maximum values. Furthermore, when a range refers to an integer, every integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe a feature or characteristic, the ranges can be combined. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges subsumed therein.
[0029] In the present invention, there is no particular limitation on the specific dispersion and stirring treatment methods.
[0030] The reagents or instruments used in the present invention without indicating the manufacturer are all conventional products that can be obtained commercially. The raw materials used in the comparative examples and the raw materials used in the parallel experiments of the examples are the same commercially available products unless otherwise specified.
[0031] The raw materials of the embodiments and comparative examples are derived from the following sources:
[0032] Spherical tungsten powder-1: The average particle size is 100nm, from Shanghai Xiangtian Nanomaterials, brand XT-W-03.
[0033] Spherical tungsten powder-2: The average particle size is 200nm, sourced from Shanghai Xiangtian Nanomaterials, brand XT-W-04.
[0034] Spherical tungsten powder-3: average particle size is 40nm, sourced from Shanghai Xiangtian Nanomaterials, brand XT-W-01.
[0035] Spherical tungsten powder-4: average particle size is 500nm, sourced from Shanghai Xiangtian Nanomaterials, brand XT-W-06.
[0036] Spherical titanium powder-1: The average particle size is 150nm, sourced from Shanghai Xiangtian Nanomaterials, brand XT-Ti-4.
[0037] Spherical titanium powder-2: The average particle size is 80nm, from Shanghai Xiangtian Nanomaterials, brand XT-Ti-2.
[0038] Spherical titanium powder-3: The average particle size is 50nm, from Shanghai Xiangtian Nanomaterials, brand XT-Ti-1.
[0039] Spherical titanium powder-4: The average particle size is 800nm, sourced from Shanghai Xiangtian Nanomaterials, brand XT-Ti-5.
[0040] Carbon nanotubes: diameter 15~30nm, length 10~20μm, sourced from Shanghai Xiangtian Nanomaterials, brand XT-C1-08.
[0041] Flaky molybdenum disulfide powder-1: The average particle size is 500nm, from Shanghai Xiangtian Nanomaterials, brand XT-MOS2-03.
[0042] Flaky molybdenum disulfide powder-2: The average particle size is 1000nm, sourced from Shanghai Xiangtian Nanomaterials, brand XT-MOS2-05.
[0043] Flaky molybdenum disulfide powder-3: The average particle size is 100nm, sourced from Shanghai Xiangtian Nanomaterials, brand XT-MOS2-01.
[0044] Flaky molybdenum disulfide powder-4: average particle size is 8000nm, sourced from Shanghai Xiangtian Nanomaterials, brand XT-MOS2-07.
[0045] Example 1
[0046] A method for preparing a tungsten target composite material comprises the following steps:
[0047] (1) Add spherical tungsten powder-1, spherical titanium powder-1, sodium carboxymethyl cellulose, and polyvinyl alcohol to water and ball mill them at a ball milling speed of 200 rpm for 6 hours to obtain a first mixed solution;
[0048] The mass ratio of the spherical tungsten powder, spherical titanium powder, sodium carboxymethyl cellulose, polyvinyl alcohol and water is 1:0.15:0.05:0.03:5.
[0049] (2) adding carbon nanotubes and γ-aminopropyltrimethoxysilane to a 0.2 mol / L nitric acid solution and stirring the mixture at 200 rpm to obtain a second mixed solution; the mass ratio of the carbon nanotubes, γ-aminopropyltrimethoxysilane, and nitric acid solution is 1:0.02:5;
[0050] (3) The first mixed solution, flaky molybdenum disulfide powder-1, and the second mixed solution were mixed evenly, ultrasonically treated at 500W for 25 minutes, and dried to obtain a precursor; the mass ratio of the first mixed solution, flaky molybdenum disulfide powder, and the second mixed solution was 1:0.025:0.25.
[0051] (4) The precursor was degreased at 600°C for 10 h and then sintered at 1200°C for 4 h to obtain a tungsten target composite material.
[0052] Example 2
[0053] A method for preparing a tungsten target composite material comprises the following steps:
[0054] (1) Add spherical tungsten powder-2, spherical titanium powder-2, sodium carboxymethyl cellulose, and polyvinyl alcohol to water and ball mill at a ball milling speed of 200 rpm for 6 hours to obtain a first mixed solution;
[0055] The mass ratio of the spherical tungsten powder, spherical titanium powder, sodium carboxymethyl cellulose, polyvinyl alcohol and water is 1:0.15:0.05:0.03:5.
[0056] (2) adding carbon nanotubes and γ-aminopropyltrimethoxysilane to a 0.2 mol / L nitric acid solution and stirring the mixture at 200 rpm to obtain a second mixed solution; the mass ratio of the carbon nanotubes, γ-aminopropyltrimethoxysilane, and nitric acid solution is 1:0.02:5;
[0057] (3) uniformly mixing the first mixed solution, the flaky molybdenum disulfide powder-2 and the second mixed solution, ultrasonic treating at 500 W for 25 min, drying to obtain a precursor; the mass ratio of the first mixed solution, the flaky molybdenum disulfide powder and the second mixed solution is 1:0.025:0.25.
[0058] (4) debinding the precursor at 600 ℃ for 10 h, sintering at 1200 ℃ for 4 h to obtain a tungsten target composite material.
[0059] Example 3
[0060] A preparation method of a tungsten target composite material comprises the following steps:
[0061] (1) ball milling spherical tungsten powder-3, spherical titanium powder-3, sodium carboxymethyl cellulose and polyvinyl alcohol into water at a ball milling speed of 200 rpm for 6 h to obtain a first mixed solution;
[0062] The mass ratio of the spherical tungsten powder, the spherical titanium powder, the sodium carboxymethyl cellulose, the polyvinyl alcohol and the water is 1:0.15:0.05:0.03:5.
[0063] (2) uniformly stirring carbon nanotubes and γ-aminopropyltrimethoxysilane into a 0.2 mol / L nitric acid solution at a stirring speed of 200 rpm to obtain a second mixed solution; the mass ratio of the carbon nanotubes, the γ-aminopropyltrimethoxysilane and the nitric acid solution is 1:0.02:5;
[0064] (3) uniformly mixing the first mixed solution, the flaky molybdenum disulfide powder-1 and the second mixed solution, ultrasonic treating at 500 W for 25 min, drying to obtain a precursor; the mass ratio of the first mixed solution, the flaky molybdenum disulfide powder and the second mixed solution is 1:0.025:0.25.
[0065] (4) debinding the precursor at 600 ℃ for 10 h, sintering at 1200 ℃ for 4 h to obtain a tungsten target composite material.
[0066] Example 4
[0067] A preparation method of a tungsten target composite material comprises the following steps:
[0068] (1) ball milling spherical tungsten powder-4, spherical titanium powder-4, sodium carboxymethyl cellulose and polyvinyl alcohol into water at a ball milling speed of 200 rpm for 6 h to obtain a first mixed solution;
[0069] The mass ratio of the spherical tungsten powder, the spherical titanium powder, the sodium carboxymethyl cellulose, the polyvinyl alcohol and the water is 1:0.15:0.05:0.03:5.
[0070] (2) adding carbon nanotubes and γ-aminopropyltrimethoxysilane to a 0.2 mol / L nitric acid solution and stirring the mixture at 200 rpm to obtain a second mixed solution; the mass ratio of the carbon nanotubes, γ-aminopropyltrimethoxysilane, and nitric acid solution is 1:0.02:5;
[0071] (3) The first mixed solution, flaky molybdenum disulfide powder-1, and the second mixed solution were mixed evenly, ultrasonically treated at 500W for 25 minutes, and dried to obtain a precursor; the mass ratio of the first mixed solution, flaky molybdenum disulfide powder, and the second mixed solution was 1:0.025:0.25.
[0072] (4) The precursor was degreased at 600°C for 10 h and then sintered at 1200°C for 4 h to obtain a tungsten target composite material.
[0073] Example 5
[0074] A method for preparing a tungsten target composite material comprises the following steps:
[0075] (1) Add spherical tungsten powder-1, spherical titanium powder-1, sodium carboxymethyl cellulose, and polyvinyl alcohol to water and ball mill them at a ball milling speed of 200 rpm for 6 hours to obtain a first mixed solution;
[0076] The mass ratio of the spherical tungsten powder, spherical titanium powder, sodium carboxymethyl cellulose, polyvinyl alcohol and water is 1:0.15:0.05:0.03:5.
[0077] (2) adding carbon nanotubes and γ-aminopropyltrimethoxysilane to a 0.2 mol / L nitric acid solution and stirring the mixture at 200 rpm to obtain a second mixed solution; the mass ratio of the carbon nanotubes, γ-aminopropyltrimethoxysilane, and nitric acid solution is 1:0.02:5;
[0078] (3) The first mixed liquid, flaky molybdenum disulfide powder-2, and the second mixed liquid were mixed evenly, ultrasonically treated at 500W for 25 minutes, and dried to obtain a precursor; the mass ratio of the first mixed liquid, flaky molybdenum disulfide powder, and the second mixed liquid was 1:0.025:0.25.
[0079] (4) The precursor was degreased at 600°C for 10 h and then sintered at 1200°C for 4 h to obtain a tungsten target composite material.
[0080] Example 6
[0081] A method for preparing a tungsten target composite material comprises the following steps:
[0082] (1) Add spherical tungsten powder-1, spherical titanium powder-1, sodium carboxymethyl cellulose, and polyvinyl alcohol to water and ball mill them at a ball milling speed of 200 rpm for 6 hours to obtain a first mixed solution;
[0083] The mass ratio of the spherical tungsten powder, the spherical titanium powder, the sodium carboxymethyl cellulose, the polyvinyl alcohol and the water is 1:0.15:0.05:0.03:5.
[0084] (2) The carbon nanotube and the γ-aminopropyltrimethoxysilane are added into a 0.2 mol / L nitric acid solution, and stirred uniformly at a speed of 200 rpm to obtain a second mixture liquid; the mass ratio of the carbon nanotube, the γ-aminopropyltrimethoxysilane and the nitric acid solution is 1:0.02:5.
[0085] (3) The first mixture liquid, the flaky molybdenum disulfide powder-3 and the second mixture liquid are mixed uniformly, and treated with ultrasonic waves at a power of 500 W for 25 min, and dried to obtain a precursor; the mass ratio of the first mixture liquid, the flaky molybdenum disulfide powder and the second mixture liquid is 1:0.025:0.25.
[0086] (4) The precursor is debound at 600 ℃ for 10 h, and then sintered at 1200 ℃ for 4 h to obtain a tungsten target composite material.
[0087] Example 7
[0088] A preparation method of a tungsten target composite material, comprising the following steps:
[0089] (1) The spherical tungsten powder-1, the spherical titanium powder-1, the sodium carboxymethyl cellulose and the polyvinyl alcohol are ball milled into water at a ball milling speed of 200 rpm for 6 h to obtain a first mixture liquid.
[0090] The mass ratio of the spherical tungsten powder, the spherical titanium powder, the sodium carboxymethyl cellulose, the polyvinyl alcohol and the water is 1:0.15:0.05:0.03:5.
[0091] (2) The carbon nanotube and the γ-aminopropyltrimethoxysilane are added into a 0.2 mol / L nitric acid solution, and stirred uniformly at a speed of 200 rpm to obtain a second mixture liquid; the mass ratio of the carbon nanotube, the γ-aminopropyltrimethoxysilane and the nitric acid solution is 1:0.02:5.
[0092] (3) The first mixture liquid, the flaky molybdenum disulfide powder-4 and the second mixture liquid are mixed uniformly, and treated with ultrasonic waves at a power of 500 W for 25 min, and dried to obtain a precursor; the mass ratio of the first mixture liquid, the flaky molybdenum disulfide powder and the second mixture liquid is 1:0.025:0.25.
[0093] (4) The precursor is debound at 600 ℃ for 10 h, and then sintered at 1200 ℃ for 4 h to obtain a tungsten target composite material.
[0094] Example 8
[0095] A method for preparing a tungsten target composite material comprises the following steps:
[0096] (1) Add spherical tungsten powder-1, spherical titanium powder-1, sodium carboxymethyl cellulose, and polyvinyl alcohol to water and ball mill them at a ball milling speed of 200 rpm for 6 hours to obtain a first mixed solution;
[0097] The mass ratio of the spherical tungsten powder, spherical titanium powder, sodium carboxymethyl cellulose, polyvinyl alcohol and water is 1:0.15:0.05:0.03:5.
[0098] (2) adding carbon nanotubes and γ-aminopropyltrimethoxysilane to a 0.2 mol / L nitric acid solution and stirring the mixture at 200 rpm to obtain a second mixed solution; the mass ratio of the carbon nanotubes, γ-aminopropyltrimethoxysilane, and nitric acid solution is 1:0.02:5;
[0099] (3) The first mixed liquid, flaky molybdenum disulfide powder-1, and the second mixed liquid were mixed evenly, ultrasonically treated at 500W for 25 minutes, and dried to obtain a precursor; the mass ratio of the first mixed liquid, flaky molybdenum disulfide powder, and the second mixed liquid was 1:0.02:0.3.
[0100] (4) The precursor was degreased at 600°C for 10 h and then sintered at 1200°C for 4 h to obtain a tungsten target composite material.
[0101] Example 9
[0102] A method for preparing a tungsten target composite material comprises the following steps:
[0103] (1) Add spherical tungsten powder-1, spherical titanium powder-1, sodium carboxymethyl cellulose, and polyvinyl alcohol to water and ball mill them at a ball milling speed of 200 rpm for 6 hours to obtain a first mixed solution;
[0104] The mass ratio of the spherical tungsten powder, spherical titanium powder, sodium carboxymethyl cellulose, polyvinyl alcohol and water is 1:0.15:0.05:0.03:5.
[0105] (2) adding carbon nanotubes and γ-aminopropyltrimethoxysilane to a 0.2 mol / L nitric acid solution and stirring the mixture at 200 rpm to obtain a second mixed solution; the mass ratio of the carbon nanotubes, γ-aminopropyltrimethoxysilane, and nitric acid solution is 1:0.02:5;
[0106] (3) The first mixed solution, flaky molybdenum disulfide powder-1, and the second mixed solution were mixed evenly, ultrasonically treated at 500W for 25 minutes, and dried to obtain a precursor; the mass ratio of the first mixed solution, flaky molybdenum disulfide powder, and the second mixed solution was 1:0.03:0.2.
[0107] (4) The precursor was degreased at 600°C for 10 h and then sintered at 1200°C for 4 h to obtain a tungsten target composite material.
[0108] Comparative Example 1
[0109] A method for preparing a tungsten target composite material comprises the following steps:
[0110] (1) Add spherical tungsten powder-1, spherical titanium powder-1, sodium carboxymethyl cellulose, and polyvinyl alcohol to water and ball mill them at a ball milling speed of 200 rpm for 6 hours to obtain a first mixed solution;
[0111] The mass ratio of the spherical tungsten powder, spherical titanium powder, sodium carboxymethyl cellulose, polyvinyl alcohol and water is 1:0.15:0.05:0.03:5.
[0112] (2) adding carbon nanotubes and γ-aminopropyltrimethoxysilane to a 0.2 mol / L nitric acid solution and stirring the mixture at 200 rpm to obtain a second mixed solution; the mass ratio of the carbon nanotubes, γ-aminopropyltrimethoxysilane, and nitric acid solution is 1:0.02:5;
[0113] (3) The first mixed liquid and the second mixed liquid were mixed evenly, subjected to ultrasonic treatment at 500 W for 25 min, and dried to obtain a precursor; the mass ratio of the first mixed liquid to the second mixed liquid was 1:0.25.
[0114] (4) The precursor was degreased at 600°C for 10 h and then sintered at 1200°C for 4 h to obtain a tungsten target composite material.
[0115] Comparative Example 2
[0116] A method for preparing a tungsten target composite material comprises the following steps:
[0117] (1) Add spherical tungsten powder-1, spherical titanium powder-1, sodium carboxymethyl cellulose, and polyvinyl alcohol to water and ball mill them at a ball milling speed of 200 rpm for 6 hours to obtain a first mixed solution;
[0118] The mass ratio of the spherical tungsten powder, spherical titanium powder, sodium carboxymethyl cellulose, polyvinyl alcohol and water is 1:0.15:0.05:0.03:5.
[0119] (2) The first mixed liquid and the flaky molybdenum disulfide powder-1 were mixed evenly, subjected to ultrasonic treatment at 500W for 25 minutes, and dried to obtain a precursor; the mass ratio of the first mixed liquid to the flaky molybdenum disulfide powder was 1:0.025.
[0120] (3) The precursor was degreased at 600°C for 10 h and then sintered at 1200°C for 4 h to obtain a tungsten target composite material.
[0121] Comparative Example 3
[0122] A method for preparing a tungsten target composite material comprises the following steps:
[0123] (1) Add spherical tungsten powder-1, spherical titanium powder-1, sodium carboxymethyl cellulose, and polyvinyl alcohol to water and ball mill them at a ball milling speed of 200 rpm for 6 hours to obtain a first mixed solution;
[0124] The mass ratio of the spherical tungsten powder, spherical titanium powder, sodium carboxymethyl cellulose, polyvinyl alcohol and water is 1:0.15:0.05:0.03:5.
[0125] (2) adding carbon nanotubes and γ-aminopropyltrimethoxysilane to a 0.2 mol / L nitric acid solution and stirring the mixture at 200 rpm to obtain a second mixed solution; the mass ratio of the carbon nanotubes, γ-aminopropyltrimethoxysilane, and nitric acid solution is 1:0.02:5;
[0126] (3) The first mixed solution, the flaky copper powder-1, and the second mixed solution were mixed evenly, subjected to ultrasonic treatment at 500 W for 25 min, and dried to obtain a precursor; the mass ratio of the first mixed solution, the flaky copper powder, and the second mixed solution was 1:0.025:0.25.
[0127] The average particle size of the flaky copper powder is 500 nm, and it is sourced from Shanghai Xiangtian Nanomaterials, with the brand name XT-Cu-05.
[0128] (4) The precursor was degreased at 600°C for 10 h and then sintered at 1200°C for 4 h to obtain a tungsten target composite material.
[0129] Comparative Example 4
[0130] A method for preparing a tungsten target composite material comprises the following steps:
[0131] (1) Add spherical tungsten powder-1, spherical titanium powder-1, sodium carboxymethyl cellulose, and polyvinyl alcohol to water and ball mill them at a ball milling speed of 200 rpm for 6 hours to obtain a first mixed solution;
[0132] The mass ratio of the spherical tungsten powder, spherical titanium powder, sodium carboxymethyl cellulose, polyvinyl alcohol and water is 1:0.15:0.05:0.03:5.
[0133] (2) adding carbon nanotubes and γ-aminopropyltrimethoxysilane to a 0.2 mol / L nitric acid solution and stirring the mixture at 200 rpm to obtain a second mixed solution; the mass ratio of the carbon nanotubes, γ-aminopropyltrimethoxysilane, and nitric acid solution is 1:0.02:5;
[0134] (3) The first mixed solution, flaky molybdenum disulfide powder-1, and the second mixed solution were mixed evenly, ultrasonically treated at 500W for 25min, and dried to obtain a precursor;
[0135] (4) The precursor was degreased at 600°C for 10 hours and then sintered at 1200°C for 4 hours to obtain a tungsten target composite material. The mass ratio of the first mixed solution, the flaky molybdenum disulfide powder, and the second mixed solution was 1:0.01:0.4.
[0136] Comparative Example 5
[0137] A method for preparing a tungsten target composite material comprises the following steps:
[0138] (1) Add spherical tungsten powder-1, spherical titanium powder-1, sodium carboxymethyl cellulose, and polyvinyl alcohol to water and ball mill them at a ball milling speed of 200 rpm for 6 hours to obtain a first mixed solution;
[0139] The mass ratio of the spherical tungsten powder, spherical titanium powder, sodium carboxymethyl cellulose, polyvinyl alcohol and water is 1:0.15:0.05:0.03:5.
[0140] (2) adding carbon nanotubes and γ-aminopropyltrimethoxysilane to a 0.2 mol / L nitric acid solution and stirring the mixture at 200 rpm to obtain a second mixed solution; the mass ratio of the carbon nanotubes, γ-aminopropyltrimethoxysilane, and nitric acid solution is 1:0.02:5;
[0141] (3) The first mixed solution, flaky molybdenum disulfide powder-1, and the second mixed solution were mixed evenly, ultrasonically treated at 500W for 25min, and dried to obtain a precursor;
[0142] (4) The precursor was degreased at 600°C for 10 hours and then sintered at 1200°C for 4 hours to obtain a tungsten target composite material. The mass ratio of the first mixed solution, the flaky molybdenum disulfide powder, and the second mixed solution was 1:0.04:0.1.
[0143] Test Case
[0144] The resistivity and elongation after fracture of the composite materials obtained in the examples and comparative examples are shown in Table 1.
[0145] Table 1
[0146]
[0147] As can be seen from Table 1, the tungsten target composite material of the present invention has excellent electrical conductivity and mechanical properties and has broad application prospects.
[0148] By comparing Example 1 with Comparative Examples 1 to 3, it can be seen that the preparation method of the present invention can significantly improve the conductivity and mechanical properties of the tungsten target composite material. When the method of the present invention is changed, the conductivity and mechanical properties will be significantly reduced.
[0149] By comparing Example 1 with Comparative Examples 4 to 5, it can be seen that the present invention significantly improves the electrical conductivity and mechanical properties by controlling the mass ratio of the first mixed liquid, the flaky molybdenum disulfide powder, and the second mixed liquid to be 1: (0.02 to 0.03): (0.2 to 0.3).
[0150] Comparing Examples 1 and 2 with Examples 3-4, it can be seen that the present invention further improves the electrical conductivity and mechanical properties by adopting spherical tungsten powder with an average particle size of 100-200 nm and spherical titanium powder with an average particle size of 80-150 nm.
[0151] By comparing Examples 1 and 5 with Examples 6 to 7, it can be seen that the present invention further improves the electrical conductivity and mechanical properties by using flaky molybdenum disulfide powder with an average particle size of 500 nm to 1000 nm.
[0152] Finally, it should be noted that the above embodiments are intended to illustrate the technical solutions of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the essence and scope of the technical solutions of the present invention.
Claims
1. A method for preparing a tungsten target composite material, characterized in that: The following steps are involved: (1) Add spherical tungsten powder, spherical titanium powder, sodium carboxymethyl cellulose, and polyvinyl alcohol to water, and mix them evenly by ball milling to obtain a first mixed solution; (2) adding carbon nanotubes and aminosilane coupling agent to the nitric acid solution and stirring evenly to obtain a second mixed solution; (3) uniformly mixing the first mixed solution, flaky molybdenum disulfide powder, and the second mixed solution, ultrasonically treating, and drying to obtain a precursor; (4) Degreasing and sintering the precursor to obtain a tungsten target composite material.
2. The method for preparing the tungsten target composite material according to claim 1, characterized in that: The average particle size of the spherical tungsten powder is 100-200 nm; The average particle size of the spherical titanium powder is 80-150 nm.
3. The method for preparing the tungsten target composite material according to claim 1, wherein: The mass ratio of the spherical tungsten powder, spherical titanium powder, sodium carboxymethyl cellulose, polyvinyl alcohol and water is 1: (0.12-0.18): (0.02-0.06): (0.02-0.05): (4-10).
4. The method for preparing the tungsten target composite material according to claim 1, characterized in that: The carbon nanotubes have a diameter of 15-30 nm and a length of 10-20 μm.
5. The method for preparing the tungsten target composite material according to claim 1, characterized in that: The aminosilane coupling agent includes at least one of γ-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, and N-(2-aminoethyl)-3-aminopropyltriethoxysilane.
6. The method for preparing the tungsten target composite material according to claim 1, characterized in that: The mass ratio of the carbon nanotubes, aminosilane coupling agent and nitric acid solution is 1: (0.01-0.03): (4-10); The molar concentration of the nitric acid solution is 0.1-1 mol / L.
7. The method for preparing a tungsten target composite material according to claim 1, characterized in that: The average particle size of the flaky molybdenum disulfide powder is 500-1000 nm.
8. The method for preparing the tungsten target composite material according to claim 1, characterized in that: The mass ratio of the first mixed liquid, the flaky molybdenum disulfide powder, and the second mixed liquid is 1: (0.02-0.03): (0.2-0.3).
9. The method for preparing a tungsten target composite material according to claim 1, wherein: The degreasing temperature is 540-580°C and the degreasing time is 6-12 hours; The sintering temperature is 1180-1220° C., and the sintering time is 2-6 hours.
10. A tungsten target composite material, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Preparation method of tungsten titanium alloy plate for sputtering target
CN102002605A
Carbon nano-tube (CNT) doping modified tungsten and explosion concretion preparation method thereof
CN103317131A